2007
DOI: 10.1016/j.jvs.2007.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Primary iliac stenting versus transluminal angioplasty with selective stenting

Abstract: The overall early clinical success rate was superior for the primary stent group. However, the initial (early) and late clinical success rates were comparable for short lesions (TASC - A and B lesions), but were inferior in selective stenting for longer lesions (TASC - C and D). Therefore, primary stenting should be offered to all TASC - C and D lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 34 publications
3
48
1
1
Order By: Relevance
“…25,26 Given the increased recoil seen with ostial iliac disease and risk of dissection with the more complex disease now more frequently encountered (ie, total occlusions, ulcerated or calcified lesions, and aneurysmal segments) the use of primary stenting for aortoiliac disease has increased. 27 A meta-analysis including 958 total patients with more complex aortoiliac disease found superior patency rates associated with primary stenting. 28 Limitations of comparing different studies of stenting for occlusive aortoiliac disease include the varied spectrum of disease complexity, the differing segments of iliac artery treated, and the use of either balloon-expandable or self-expanding nitinol stents.…”
Section: Aortoilliac Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Given the increased recoil seen with ostial iliac disease and risk of dissection with the more complex disease now more frequently encountered (ie, total occlusions, ulcerated or calcified lesions, and aneurysmal segments) the use of primary stenting for aortoiliac disease has increased. 27 A meta-analysis including 958 total patients with more complex aortoiliac disease found superior patency rates associated with primary stenting. 28 Limitations of comparing different studies of stenting for occlusive aortoiliac disease include the varied spectrum of disease complexity, the differing segments of iliac artery treated, and the use of either balloon-expandable or self-expanding nitinol stents.…”
Section: Aortoilliac Diseasementioning
confidence: 99%
“…28 Limitations of comparing different studies of stenting for occlusive aortoiliac disease include the varied spectrum of disease complexity, the differing segments of iliac artery treated, and the use of either balloon-expandable or self-expanding nitinol stents. 27,29 There are currently no randomized data comparing outcomes of aortoiliac stenting with these 2 types of stents directly. Given the lack of external compressive forces and their relatively nontortuous course, iliac artery stenting with balloon-expandable stents offer enhanced radial strength and can be more precisely positioned to treat ostial disease.…”
Section: Aortoilliac Diseasementioning
confidence: 99%
“…The 3-year primary patency rates in PTA group alone were less than 60% [31,32] ; while primary patency rates in PTA plus stenting group reached up to 90% [33][34][35]. Bosch and colleagues [36] found that the technical success rate of iliac angioplasty plus stenting was higher than that in PTA group alone but without statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…[86,87] Due to increased recoil seen with ostial iliac disease, the use of primary stenting has been increased for aortoiliac disease. [88] Primary stenting shows high patency rates in a meta-analysis study on 958 total patients suffering from more complex aortoiliac disease. [89] Limitations of comparing different studies related to stenting for occlusive aortoiliac disease include i.e.…”
Section: Figure5 An Intraoperative Photograph Of a Right Femoral To mentioning
confidence: 99%
“…complexity of disease, the differing segments of iliac artery to be treated, and the use of either balloon-expandable or self-expanding nitinol stents. [90,91] Currently there are no randomized data available regarding comparing outcomes of aortoiliac stenting with these 2 types of stents. Self-expanding stents are good to avoid arterial rupture.…”
Section: Figure5 An Intraoperative Photograph Of a Right Femoral To mentioning
confidence: 99%